Indonesian Version of Swedish Occupational Fatigue Inventory (SOFI): Validity and Reliability Test of Worker’s Fatigue Assessment Instrument - Afrionaldi Suparman; Suryo Wibowo; Aria Kekalih; M Ilyas; Amilya Agustina (The Indonesian Journal of Community and Occupational Medicine, 2022)
Background: The Swedish Occupational Fatigue Inventory (SOFI) is an instrument to assess a person’s fatigue, which is not limited to workers of a company, but can also be used for the general public. SOFI can determine fatigue from physical, cognitive and psychosocial conditions.1 This study aims to translate the instrument so that it can be used in Indonesia, then assess its validity and reliability.Methods: This study was conducted using a 10-step transcultural adaptation method from ISPOR followed by item validity and reliability tests on 224 workers at a geothermal company in Indonesia. Item-total correlation and Confirmatory Factor Analysis was performed using online version 0.14.3 of JASP statistic program. And for reliability test using SPSS tool.Results: Swedish Occupational Fatigue Inventory (SOFI) has been adapted into an Indonesian version through the ISPOR transcultural adaptation method. All items in the Indonesian version of SOFI which amounted to 20 items proved the validity and reliability of this questionnaire was very good (α-Cronbach 0.969) and the Confirmatory Factor Analysis test showed: Factor model (224, p < 0,001) = 337.649, CFI = 0,958, NFI = 0,924, RFI = 0,909, IFI = 0,958, TLI = 0,950, dan RMSEA = 0,070, 90% CI: 0,060 – 0,081. Fit indices results had acceptable model fits corresponding to the structure of the original instrument. Item-rest correlation range from 0.321 to 0.847, these results reveal that each item-rest correlation is extremely strong.Conclusion: The Indonesian version of SOFI is proven to have good validity and reliability as an instrument for assessing fatigue/work fatigue for workers in Indonesia.